The Linguistic landscape of Accommodation Businesses in Ambon City, Maluku, Indonesia - Sari, Hindri Febri Ana; Nusi, Ahmad; Persulessy, Sylvia Irene; Hahury , Jessy J (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
This study explores the linguistic landscape of accommodation businesses in Ambon City, Maluku, Indonesia, highlighting the significant role of public signage in enhancing the tourist experience. Recognized for its rich cultural heritage and robust tourism infrastructure, Ambon boasts 71 tourist attractions and 60 hotels that cater to diverse visitors. This research employs a mixed-methods approach, analyzing 150 public signs across various accommodation venues with an emphasis on their linguistic characteristics and effectiveness in communication. Preliminary findings indicate that 68% of public signs in Ambon are monolingual, primarily in Bahasa Indonesia, while only 32% incorporate multiple languages, predominantly English, to accommodate international tourists. Furthermore, among the multilingual signs, 75% effectively facilitated navigation and communication for non-Indonesian speakers, significantly improving the overall tourist experience. Statistical analysis reveals a direct correlation between the presence of multilingual signage and positive tourist feedback, with 85% of respondents indicating a preference for signs that provide information in multiple languages. The study concludes that enhancing the linguistic diversity of public signs not only promotes Ambon as an accessible tourist destination but also reinforces its brand identity as a culturally rich and welcoming locale. By adopting a more inclusive approach to public signage, Ambon can further attract and accommodate a wider range of visitors, ultimately contributing to the growth and sustainability of its tourism sector.